POUZOLZIA FLORESIANA (URTICACEAE), A NEW SPECIES FROM FLORES, NUSA TENGGARA TIMUR (LESSER SUNDA ISLANDS), INDONESIA - Wilmot-Dear, C. M.; Friis, I. (Edinburgh Journal of Botany, 2012)
Pouzolzia floresiana Friis & Wilmot-Dear (Urticaceae) is described and illustrated on the basis of a single collection from the western part of the Indonesian island of Flores. The species is a thick-stemmed herb, similar in habit to Pouzolzia thailandica, but differs in having axillary flower clusters and broadly winged fruiting perianths. The description of the new species supplements a revision of the Old World taxa of Pouzolzia by the two authors published in 2006.
Keywords: Description; Flores; Indonesia; new species; Pouzolzia; Pouzolzia floresiana; taxonomy; Urticaceae